2019
DOI: 10.1038/s41598-019-41403-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HIV-1 integrase potency of methylgallate from Alchornea cordifolia using in vitro and in silico approaches

Abstract: According to the 2018 report of the United Nations Programme on HIV/AIDS (UNAIDS), acquired immune deficiency syndrome (AIDS), a disease caused by the human immunodeficiency virus (HIV), remains a significant public health problem. The non-existence of a cure or effective vaccine for the disease and the associated emergence of resistant viral strains imply an urgent need for the discovery of novel anti-HIV drug candidates. The current study aimed to identify potential anti-retroviral compounds from Alchornea c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 53 publications
(59 reference statements)
0
22
0
Order By: Relevance
“…In the central and coastal regions of Cameroon, Dibong et al [6] reported that the leaves of this plant are used for the treatment of anemia. This plant has many order traditional applications, including treatment of pain and inflammatory disorders, hormonal-related gynecological disorders, infertility, urinary, respiratory and intestinal problems as well as malaria-like fevers and anti-HIV1 integrase activity [7][8][9][10][11][12][13][14][15][16]. Earlier studies on the chemical constituents of A. cordifolia identified compounds such as tannins, phenolic acids, flavonoids and alkaloids [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the central and coastal regions of Cameroon, Dibong et al [6] reported that the leaves of this plant are used for the treatment of anemia. This plant has many order traditional applications, including treatment of pain and inflammatory disorders, hormonal-related gynecological disorders, infertility, urinary, respiratory and intestinal problems as well as malaria-like fevers and anti-HIV1 integrase activity [7][8][9][10][11][12][13][14][15][16]. Earlier studies on the chemical constituents of A. cordifolia identified compounds such as tannins, phenolic acids, flavonoids and alkaloids [11].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies on the chemical constituents of A. cordifolia identified compounds such as tannins, phenolic acids, flavonoids and alkaloids [11]. The varied popular uses of different parts of A. cordifolia have led to many modern pharmacological investigations like antibacterial [16], antifungal [17], spasmolytic [18] and reproductive activities [13].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, in this review, we discuss some recent highlights in medicinal chemistry research (2016–2020) in which researchers based in South Africa have made a significant contribution through medicinal chemistry methodology. Therefore, this review excludes recent contributions made in natural products chemistry . While substantial focus in South African medicinal chemistry is devoted to neurological disorders and cancer, this review will focus on those studies with promise against infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Acquired Immune Deficiency Syndrome (AIDS) is one of the major viral infections ravaging the world; around 76.1 million people have been infected since the first report in 1981 [1]. According to the report of the Cameroon Population Based HIV Impact Assessment (CAMPHIA) in 2018, viral prevalence in Cameroon is 3.4% [2] and about 37 million people around the world are currently living with the infection [1].…”
Section: Introductionmentioning
confidence: 99%
“…Acquired Immune Deficiency Syndrome (AIDS) is one of the major viral infections ravaging the world; around 76.1 million people have been infected since the first report in 1981 [1]. According to the report of the Cameroon Population Based HIV Impact Assessment (CAMPHIA) in 2018, viral prevalence in Cameroon is 3.4% [2] and about 37 million people around the world are currently living with the infection [1]. The absence of vaccines and associated resistance of virus to antiretroviral drugs [1] have contributed to the impairment of most patient’s defense system by opportunistic bacterial infections such as tuberculosis and other bacterial pneumonia infections [3].…”
Section: Introductionmentioning
confidence: 99%